(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
Centro studi interateneo Notariorum Itinera – headquarter at the University of Genoa and subsidiaries at the Universities of Bari, Bologna, Catanzaro, Milan Statale, Pavia, Rome Tor vergata, Salerno and Turin – was formally established in May 2017. The aim of Centro studi is to study notary, Italian and european notarial registers and, more widely, all the related records in order to get a full knowledge – without chronological and geographical limits – of the activity of this professional category. The paper focuses on the status questionis and illustrates the first results of ongoing studies. DOI 10.17464/9788867742752